Investigating the Relationship Between Selective Attention and Cognitive Flexibility With Balance in Patients With Relapsing-Remitting Multiple Sclerosis - Vali Shiri; Mahbubeh Emami; Esmail Shiri (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective Multiple Sclerosis (MS) is known as one of the most common neurological disorders that affect patients’ lives tremendously. These people experience various dysfunctions. One of the most common problems in patients with MS is a balance deficit, which limits the participation and increases the risk of falling. Recently various studies were focused on finding the causes of this imbalance. On the other hand, these patients experience cognitive problems, such as attention deficit and cognitive flexibility. Therefore, the aim of this study was to investigate the relationship between cognitive flexibility and selective attention with balance in patients with relapsing-remitting MS. Materials & Methods This study is a cross-sectional case study. The statistical population in this study was patients with MS who referred to Kashani Hospital and Alzahra Isfahan Hospital in 1395 for inclusion in the study, based on available sampling method. MS diagnosis was performed in these centers with the approval of at least one adult neurologist. Finally, 40 patients with MS were selected by convenient sampling. A written consent form was received from all the families and the patients with MS themselves for participation in the study. All patients were kept confidential in the study, and they were allowed to leave during the study if they refused. The inclusion criteria to participate in the study were: satisfaction of patients to participate in the plan, the individual received a diagnosis of relapsing-remitting MS from those who were referred to Al-Zahra and Kashani hospitals in Isfahan, aged 20 to 40 years, at least two attacks in last 24 months, a score of less than 5.5 in EDSS was associated with a moderate degree of MS due to the severity of the disability and the symptoms of the disease, having sufficient insight and the ability to collaborate in the study through the MMSE test. The exclusion criteria of the study were: dissatisfaction of the patients with the continuation of the study, presence and participation in similar investigations in the last three months that were performed intermittently on executive functions, the presence of visual and auditory impairment, recurrence and severity of MS, disability from moderate to severe, and any abnormalities such as seizure. After that test EDSS, Stroop color-word test, Wisconsin card sorting, and Berg Balance Scale were completed by patients with MS. The results of the tests of executive function and balance were analyzed using SPSS20 software for the presence or absence of the relationship between executive function is determined by the balance. To analyze the data, Pearson correlation coefficient and multiple regression and analysis of variance with repeated measures at the level of 0.05. Results The results of this study demonstrate a significant relationship between selective attention and balance problem (P<0.05). However, there is no significant relationship between cognitive flexibility and balance (P<0.05). As well as the selective attention can predict the balance problem (P<0.05) (P<0.01). Conclusion A significant relationship between selective attentions to balance demonstrates that appropriately designed interventions to repair the attention, can decrease the balance problem in patients with MS. One of the possible reasons for this relationship can be found in the brain system that attention circuits are interacting with equilibrium systems, and any defect in selective attention leads to a loss of balance. Patients with MS experience constant imbalance due to cerebral plaques and relapsing-remitting periods, and in addition to rehabilitation of the balance system, cognitive systems such as attention should be treated.